2021
DOI: 10.3390/cancers13215463
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Based on Morphological Features Enables Classification of Primary Intestinal T-Cell Lymphomas

Abstract: The aim of this study was to investigate the feasibility of using machine learning techniques based on morphological features in classifying two subtypes of primary intestinal T-cell lymphomas (PITLs) defined according to the WHO criteria: monomorphic epitheliotropic intestinal T-cell lymphoma (MEITL) versus intestinal T-cell lymphoma, not otherwise specified (ITCL-NOS), which is considered a major challenge for pathological diagnosis. A total of 40 histopathological whole-slide images (WSIs) from 40 surgicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Our work represents the first pixel-level assessment of the size and shape differences between DLBCL and non-DLBCL. Prior studies that quantitatively assessed interpretable morphologic features in lymphoma diagnosis have used a smaller number of cases and fewer diagnostic categories (Gupta et al 2010; Lesty et al 1986; W.-H. Yu et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Our work represents the first pixel-level assessment of the size and shape differences between DLBCL and non-DLBCL. Prior studies that quantitatively assessed interpretable morphologic features in lymphoma diagnosis have used a smaller number of cases and fewer diagnostic categories (Gupta et al 2010; Lesty et al 1986; W.-H. Yu et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that morphometric parameters can be used to classify primary intestinal T-cell lymphoma. 23 Here, we analyzed the disease prognosis based on objective morphometric parameters extracted from tens of thousands of nuclei among 103 MCL patients to derive a significant and human-interpretable result.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al collected 40 histological WSIs for dataset training in a DNN. They succeeded in extracting picture characteristics and categorizing T-cell lymphomas, such as intestinal T-cell lymphoma, which pose difficulties in morphologic diagnosis [ 46 ].…”
Section: Current Applications Of Ai In Hematologic Cytologymentioning
confidence: 99%